2005
DOI: 10.1002/chem.200500628
|View full text |Cite
|
Sign up to set email alerts
|

The Heat of Formation of the Uranyl Dication: Theoretical Evaluation Based on Relativistic Density Functional Calculations

Abstract: By using a set of model reactions, we estimated the heat of formation of gaseous UO2(2+) from quantum-chemical reaction enthalpies and experimental heats of formation of reference species. For this purpose, we performed relativistic density functional calculations for the molecules UO2(2+), UO2, UF6, and UF5. We used two gradient-corrected exchange-correlation functionals (revised Perdew-Burke-Ernzerhof (PBEN) and Becke-Perdew (BP)) and we accounted for spin-orbit interaction in a self-consistent fashion. Inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 51 publications
2
14
0
Order By: Relevance
“…The difficulty of measuring the formation enthalpy of gas phase actinyl ions might be, in part, the cause of this discrepancy. 59 This difficulty is even stronger in the case of the dication since it involves measuring the second ionization energy of the gas phase actinyl. Our value for the hexavalent actinyls approaches the value of Marcus especially since our H [AnO 2 ] 2+ + could be missing a small many-body contribution in the first-second shell interaction.…”
Section: A Hydration Enthalpiesmentioning
confidence: 99%
“…The difficulty of measuring the formation enthalpy of gas phase actinyl ions might be, in part, the cause of this discrepancy. 59 This difficulty is even stronger in the case of the dication since it involves measuring the second ionization energy of the gas phase actinyl. Our value for the hexavalent actinyls approaches the value of Marcus especially since our H [AnO 2 ] 2+ + could be missing a small many-body contribution in the first-second shell interaction.…”
Section: A Hydration Enthalpiesmentioning
confidence: 99%
“…The difficulties associated with the accurate quantification of gas phase formation enthalpy of actinides may be behind this substantial gap between experimental measurements. 76 The TIP4P water model aside, we must point out that the H [UO] 2+ 2 (aq) estimation might be missing a small manybody contribution due to the first-second shell hydration. 49 Therefore, our ∆H hyd could be slightly overestimated, which suggested that our theoretical estimation is much closer to Marcus' value.…”
Section: A Hydration Enthalpymentioning
confidence: 99%
“…Recent remarkable examples are re-evaluations of the first ionization potential of gaseous UO 2 4 and PuO 2 ; 5,6 these works were motivated by a disagreement between high-level theoretical results and long accepted experimental values. 3,7,8 In a preceding publication 9 we reported a theoretically estimated value for the heat of formation of gaseous uranyl, UO 2 21 , derived from quantum-chemical reaction enthalpies and well-known experimental heats of formation of reference uranium compounds. We employed a series of model reactions and we averaged the corresponding results to obtain a theoretical result with error bars.…”
Section: Introductionmentioning
confidence: 99%